Fenomena Penundaan Pembagian Waris di Kalangan Keluarga Ulama Kabupaten Hulu Sungai Utara - Ahmad Manfaluti; Akhmad Haries; Mukhtar Muhammad Salam (Journal on Education, 2023)
The widespread phenomenon of indefinite delays in inheritance distribution in North Hulu Sungai Regency, which runs counter to the idea of the Islamic inheritance system, serves as the inspiration for this study. The next issue is that ulama, who are knowledgeable about Islamic law, also continue this practice. Thus, this research aims to explore the reasons behind the practice of postponing inheritance among ulama families. Choosing the site in North Hulu Sungai Regency due to its reputation as the second Islamic residential school city in South Kalimantan Province, following Martapura, and the large number of ulama who were born and raised in this region. This research is included in the type of empirical research using a qualitative approach because all the data is presented in the form of descriptive information and statements. The data sources used are primary and secondary data, while the data collection technique uses direct interviews with respondents, observation, and documentation. Based on the research that has been carried out, the results obtained are of the ten ulama in North Hulu Sungai Regency who have been interviewed, as many as eight people implemented a delay in distributing inheritance, while the remaining two people immediately distributed inheritance to heirs after the death of the testator. The ulama provide a variety of explanations, including the fact that one parent is still alive, the inheritance consists of a house and property, the heirs are firmly established, and the heir regarded as the most meritorious in the family controls the inheritance.